La naissance du quartier de la Poudrière (1) - Clairoux, Benoit (Les Argoulets, 2024)
Keywords: Armes; Femmes; Guerre; Verdun

Sur le chemin des tanks - Boucley, Pierre (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Armes; Guerre; Usines Angus

« Others of more entreprise »: Thomas Morland and the Formation of Montreal Rolling Mills, 1858-1868 - Mathieu, Jean-Philip (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Montreal Rolling Mills; Quartiers

De Lorimier 1895-1909 (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-24-00
Keywords: Chaussure; De Lorimier (village); Parcs; Usines Angus

Le Plateau industriel (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-22-00
Keywords: Alimentation; Chaussure; Grèves; Plateau Mont-Royal (arrondissement); Travail; Vêtements

L'histoire des boissons gazeuses Corona - Clairoux, Benoît (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Alimentation; Verdun

L’héritage contrasté de l’âge d’or du pétrole : histoire et évolution des paysages de l’est de Montréal - Hatton-Proulx, Clarence; Mercure Jolette, Frédéric; Van Neste, Sophie L. (Recherches sociographiques, 2023)
Keywords: Anjou; Montréal-Est; Paysages; Pollution; Pétrole

“La Grève de la fierté”: Resisting Deindustrialization in Montréal’s Garment Industry, 1977–1983 - Laframboise, Lauren (Labour / Le Travail, 2023)
issued: 2023-23-00
Keywords: Femmes; Grèves; International Ladies' Garment Workers' Union; Vêtements

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

John George Savage. Un habitant notable de Dorval/John George Savage. A notable Dorval resident - Nieuwendyk, Dick (Héritage Dorval, 2023)
Keywords: Anglicans; Dorval; Peinture

Fabriquer la tradition canadienne-française : le tabac canadien et la construction de l’identité canadienne-française, 1880-1950 - Rudy, Jarrett (Écrire la ville. Pouvoirs, urbanités et modernités dans l’espace québécois (XIXe-XXe siècles), 2023)
Keywords: Tabac

Le boulevard Saint-Laurent et son histoire-(suite 1) - Tessier, Stéphane (Il était un fois... Montréal Nord, 2023)
issued: 2023-21-00
Keywords: Juifs; Saint-Laurent (rue)

Le travail traditionnel dans les carrières de calcaire de Montréal: un prélude à la carrière Rhéaume - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Artisans; Carrière; Charretiers; Travail

Dictionnaire historique des gens du livre au Québec - Aubin, Paul; Luneau, Marie-Pier; Vincent, Josée (Les Presses de l'Université de Montréal, 2022)
Keywords: Imprimerie

Le travail du métal à Montréal au XVIIe siècle. Des métiers '' d’avenir '' ? - Blouin, Sonia (2022)
issued: 2022-24-00
Keywords: Armuriers; Fer et acier

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

Patrimoine et développement local: le cas de l'édifice RCA - Dambre-Sauvage, Laurent (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Patrimoine

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

“Perfect Dry Plates for Canada”: Gelatine Dry-Plate Manufacturing in Canada in the Late Nineteenth Century - Perry, Shannon (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine, 2022)
Keywords: Notman; William; Photographie; Publicité

DUPUIS, JOSEPH-NARCISSE (Dictionnaire biographique du Canada, 2022)

Petite histoire du Cercle de Fermières de Montréal-Nord - Savard, Marielle (Il était une fois...Montréal-Nord, 2022)
issued: 2022-22-00
Keywords: Clubs; Femmes; Montréal-Nord; Quartiers

Prohibition-Brasserie Chapman-Microbrasseries - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2022)
Keywords: Alcool; Brasserie; Prohibition

Histoire du site des moulins du Sault-au-Récollet - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-23-00
Keywords: Meunerie; Patrimoine; Sault-au-Récollet

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
issued: 2022-24-00
Keywords: Routes; Saint-Laurent (rue)

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

L’importance des métaux dans une ville naissante : les artisans du métal dans l’espace social et urbain de Montréal de 1642 à 1701 - Blouin, Sonia (Université de Sherbrooke, 2021)
Keywords: Artisans; Fer et acier; Travail

La boulangerie Le Pain moderne canadien de Montréal. Les promesses du pain industriel - Burgess, Joanne (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Boulangerie

BRAINERD, THOMAS CHALMERS - Cloutier, J.-Roger (Dictionnaire biographique du Canada, 2021)

Au croisement de la perte de mémoire et de la créativité communautaire: de nouvelles innovations dans les anciens ateliers ferroviaires de Pointe-Saint-Charles - Elliott, Andrew (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Canadien National; Chemins de fer; Conservation; Grand Tronc; Patrimoine

Les minoteries du canal de Lachine - Gelly, Alain (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie flour Mills

Petites et grandes boulangeries. La fabrication du pain dans le quartier Centre-Sud de Montréal - Giroux, Éric (Cap-aux-Diamants, 2021)
issued: 2021-23-00
Keywords: Alimentation; Boulangerie; Centre-sud (quartier)

Gendered labour, immigration, and deindustrialization in Montreal's garment industry - Laframboise, Lauren (Université Concordia, 2021)
Keywords: Femmes; Grèves; Travail; Vêtements

Produits Familex: de l'usine à votre porte - Landreville, Julie (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Commerce de détail; Pharmacie; Produits pharmaceutiques

DOUGALL, JOHN REDPATH - MacLeod, Roderick (Dictionnaire biographique du Canada, 2021)

De la barge aux usines: les mécanismes de déchargement du charbon au canal de Lachine - Paquet, Lucie (Bulletin de l'AQPI, 2021)
issued: 2021-21-00
Keywords: Lachine (canal); Montreal Rolling Mills

Pour les femmes, par les femmes : une histoire entrepreneuriale de la presse féminine québécoise au tournant du XXe siècle - Rocher-Lewis, Delphine (Université du Québec à Montréal, 2021)
Keywords: Barry; Robertine; Bélanger; Georgina (De Montreuil; Gaétane / Bélanger; Georgine); Femmes; Journalistes; Marchand-Dandurand; Joséphine

Le Plateau agricole (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2020)
issued: 2020-24-00
Keywords: Alimentation; Baron (côte à); Côtes; Institut des sourdes-muettes; Jardins; Meunerie; Plateau Mont-Royal

Saveur café (Mémoire vivante, 2020)
issued: 2020-24-00
Keywords: Alimentation; Cafés; Restaurant; Épicerie

Saveur café: À l'origine du café de Gérard Van Houtte - Bizier, Hélène-Andrée (Mémoire vivante, 2020)
issued: 2020-24-00
Keywords: Alimentation; Cafés; Restaurant; Épicerie

La Brasserie Dow. Tome 2: La chute - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2020)
Keywords: Brasserie; Dow (brasserie)

Futur parc sur la rue Marcel-Pepin. Un lieu riche en histoire - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2020)
Number: 1
Keywords: Chemins de fer; Hôpitaux; Itinérance; Usines Angus; Variole; Épidémies

"Ici, c'est le salon du peuple!" : microbrasseries, bières artisanales et communautés de consommation au Québec - Francoeur, Iannick (Université Laval, 2020)
Keywords: Brasserie; Molson (brasserie); National Breweries Limited

Montréal en 1919 : industries, travail et espaces résidentiels - Girard, David (Université du Québec à Montréal, 2020)
Keywords: Tramways; Travail

Une amitié nécessaire: entraide et fraternité dans le champ des comic books québécois (1984-1995) - Rioux, Philippe (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 2020)
Keywords: Bande dessinée; Librairie; Magasins; Édition

Seam Stress: Garment Work and Gendered Labour Struggle in 1980s Montreal - Siaw, Leona (Université Concordia, 2020)
Keywords: Femmes; Grèves; Textile

Transmettre le savoir et une vision du Canada aux jeunes Québécois: une étude de « L’Encyclopédie de la jeunesse » (1923) de la Société Grolier de Montréal - Bernier, Kristina (Université de Sherbrooke, 2019)
Keywords: Action française (L'); Nationalisme; Édition

A Voice of English-Montreal. The First Twenty Years of Véhicule Press, 1973-1993 - Hemond, Amy (Université McGill, 2019)
Keywords: Imprimerie; Poésie; Édition

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Angelina Di Bello: une grande dame de la couture - Mathieu, Jocelyne (Cap-aux-Diamants, 2019)
issued: 2019-23-00
Keywords: Confection; Vêtements

Legal Persons and Asset Management Strategy: William Clendinneng and the Canada Pipe and Foundry Company - Simeone, Daniel (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Banque du Peuple; Banques; Fer et acier; Mouleurs

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

RUBENSTEIN, LOUIS - Vigneault, Michel (Dictionnaire biographique du Canada, 2019)

Commerces du Plateau: d'hier à aujourd'hui (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2018)
issued: 2018-24-00/2019-24-00
Keywords: Alimentation; Artisans; Bijouterie; Chaussure; Commerce de détail; Magasins; Mont-Royal (rue); Plateau Mont-Royal; Quartiers; Quincaillerie; Rues; Saint-Denis (rue); Saint-Laurent (rue); Épicerie

Les céramiques et les réseaux maritimes du fort de Ville-Marie, Montréal, 1642-1688 - Bourgela, Samuel (Université de Montréal, 2018)
Keywords: Marchands; Port; Poterie

La filature Hudon - Charbonneau, Réjean; Cousineau, André (D'une track à l'autre, 2018)
Number: 3
Keywords: Hochelaga (quartier); Quartiers; Textile; Travail

La brasserie Dow. Tome 1: L'ascension - Charlebois, Paul-Yvon; Daignault, Sylvain (Les Éditions GID, 2018)
Keywords: Brasserie; Dow (brasserie)

Through the Mill: Girls and Women in the Quebec Cotton Textile Industry, 1881-1951 - Cuthbert Brandt, Gail (Baraka Books, 2018)
Keywords: Femmes; Grèves; Textile; Travail

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Les défis de la sauvegarde du patrimoine à la Société d'histoire d'Ahuntsic-Cartierville - Labarussias, Jordane (Histoire Québec, 2018)
Number: 2
Keywords: Ahuntsic; Armes; Cartierville; Conservation; Femmes; Forts; Guerre; Histoire; Patrimoine; Quartiers; Sault-au-Récollet

Une note musicale! (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-24-00/2018-24-00
Keywords: Chanson; Musicien; Musique

Nourrir le quartier, nourrir la ville - Burgess, Joanne; Giroux, Éric (Écomusée du fier monde, 2017)
Keywords: Alimentation; Biscuiterie; Boulangerie; Brasserie; Centre-sud (quartier); Magasins; Marchés; Quartiers; Épicerie

Eusèbe Senécal imprimeur-éditeur 1860-1902 - Cudia, Caroline (Université du Québec à Montréal, 2017)
Keywords: Imprimerie; Revue canadienne (La); Senécal; Eusèbe; Édition

Les tanneries de Saint-Henri: de Jean-Talon à l'échangeur - Giasson, Guy (Histoire Québec, 2017)
Number: 1
Keywords: Artisans; Fourrure; Quartiers; Saint-Henri; Tannerie

Angus: ADN et mutations génétiques - St-Cyr, Pierre (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
issued: 2017-21-00
Keywords: Canadien Pacifique; Chemins de fer; Conservation; Patrimoine; Usines Angus

GORDON, SIR CHARLES BLAIR - Brown, Robert Craig (Dictionnaire biographique du Canada, 2016)

Confitures et marinades Raymond: faites pour plaire! - Giroux, Éric (Bulletin de l'Association québécoise pour le patrimoine industriel, 2016)
issued: 2016-21-00
Keywords: Alimentation; Expositions; Musées; Écomusée du fier monde

La Centrale d’artisanat du Québec à Montréal - Mathieu, Jocelyne (Les Cahiers des Dix, 2016)
Number: 70
Keywords: École des Beaux-Arts; École des arts graphiques; École du meuble

Au chant des ailes des moulins - Royer, Martin (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Meunerie

A Locational History of Fashion in Montréal - Sark, Katrina; Bélanger-Michaud, Sara Danièle (University of Chicago Press, 2016)
Keywords: Cinéma; Confection; Costume; Expositions; Musique; Musée McCord; Musée des Beaux-Arts; Musées; Vêtements

100 tonnes d'explosifs stockés sur l'avenue Dunlop! Intolérable! - Lester, Normand (Mémoire vivante, 2015)
issued: 2015-24-00/2016-24-00
Keywords: Armes; Forts; Rébellions

1900. Pourquoi pas un gram-o-phone Berliner? - P. Bouliane, Sandria (De la Belle époque à la Crise. Chroniques de la vie culturelle à Montréal, 2015)
Keywords: Chanson; Gramophone; Musique

LEVINSON, SOLOMON - Lapidus, Steven (Dictionnaire biographique du Canada, 2014)

Émergence et évolution d’une profession artistique: les dessinateurs de presse entre 1880 et 1914 à Montréal - Danaux, Stéphanie (Médias 19, 2013)
Keywords: Caricature; Gravure; Patrie (La)

Esthétique de la typographie: Roland Giguère, les Éditions Erta et l'École des arts graphiques - Dulude, Sébastien (Nota Bene, 2013)
Keywords: École des arts graphiques; Édition

Les couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Septentrion, 2013)
Keywords: Confection; Femmes

GRAHAM, HUGH, 1er baron ATHOLSTAN - Raudsepp, Enn (Dictionnaire biographique du Canada, 2013)

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

Pointe-Saint-Charles: histoire de locomotives - Bélisle, Jean (Bulletin de l'Association québécoise pour le patrimoine industriel, 2012)
issued: 2012-21-00
Keywords: Canadien National; Chemins de fer; Grand Tronc

Le système régional d’innovation de l’aéronautique à Montréal: entre dynamiques territoriales et sectorielles - Ben Hassen, Tarek (Université du Québec à Montréal, 2012)
Keywords: Avionnerie

Made in Montreal: A Study of Geography and Priorities of Small Urban Manufacturers in Post-Industrial Montreal - Carruthers, Alex (Université McGill, 2012)

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

Sarto Desnoyers, l'homme aux tâches multiples 1904-1996 / Sarto Desnoyers, Jack of All Trades 1904-1996 - Garneau, André (Héritage Dorval, 2012)
Keywords: Chevaux; Dorval; Hockey; Maires; Palestre nationale; Pharmacie; Produits pharmaceutiques

Héritage Dorval 2011 (Héritage Dorval, 2011)
Keywords: Bijouterie; Chaussure; Dentistes; Hôtellerie; Magasins; Quincaillerie; Restaurant; Électricité

Industrial Land Retention in Two Cities: Municipal Strategies to Retain Manufacturing in Industrial Districts in Montreal and New York City - Charters, Stephen (Université McGill, 2011)
Keywords: Arrondissements; LaSalle; Le Sud-Ouest (arrondissement)

Grandeur et déclin de la pétrochimie sur le territoire historique de la Pointe-aux-Trembles et de Montréal-Est - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2011)
Keywords: Montréal-Est; Pointe-aux-Trembles; Pétrole; Quartiers

Intervention publique sur le développement de grappes industrielles au Québec - Doloreux, David; Tremblay, Diane-Gabrielle; Klein, Juan-Luis; Dionne, Steve; Ben Hassen, Tarek (The Canadian Geographer / Le Géographe canadien, 2011)
issued: 2011-24-00

Étude urbaine d'un îlot du faubourg Saint-Laurent: la confection sur la Main, 1880-1939 - Lacaille, Marie-Ève (Université du Québec à Montréal, 2011)
Keywords: Confection; Faubourgs; Juifs; Quartiers; Rues; Saint-Laurent (quartier); Saint-Laurent (rue)

Le moulin de Pointe-Claire, 1710-2010 / 1710-2010, The Pointe-Claire Mill - Arsenault, Claude (Société pour la sauvegarde du patrimoine de Pointe-Claire, 2010)
Keywords: Meunerie; Pointe-Claire

Le moulin à vent de Pointe-aux-Trembles - Belzil, Claude (Atelier d'histoire de Pointe-aux-Trembles avec le concours de l'arrondissement Rivière-des-Prairies - Pointe-aux-Trembles de la ville de Montréal, 2010)
Keywords: Conservation; Meunerie; Patrimoine; Pointe-aux-Trembles

Éditeur de livres et de brochures - Bennett, Paul (Le Devoir: un siècle québécois, 2010)
Keywords: Devoir (Le); Édition

L'atelier des Écores (1792-1830): Une entreprise artisanale - Chagnon, Joanne (Université du Québec à Montréal, 2010)
Keywords: Artisans; Arts sacrés; Pépin; Joseph; Quévillon; Louis; Sculpture

Vapeur, thermoélectricité et hydroélectricité comme force motrice le long du corridor industriel du canal de Lachine, des années 1850 à la Seconde Guerre mondiale - Gelly, Alain (Université Laval, 2010)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

Aspects démographiques de la vie des couturières de Montréal au XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2010)
issued: 2010-24-00
Keywords: Confection; Femmes

La production du manuel scolaire congréganiste au Québec. Le cas de l'atelier d'imprimerie des Frères des écoles chrétiennes, 1891-1918 - Laforce, Guillaume (Université Laval, 2010)
Keywords: Communautés religieuses; Frères des écoles chrétiennes; Imprimerie

Angus Shop - Leduc, Michael (Michael Leduc, 2010)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

1870: du journal d'opinion à la presse de masse, la production industrielle de l'information - Leroux, Éric (Petit musée de l'impression et Centre d'histoire de Montréal, 2010)
OCLC: 676809390
Keywords: Asselin; Olivar; Bourassa; Henri; Buies; Arthur; Devoir (Le); Idéologies; Imprimerie; Journalistes; Lanterne (La); Lovell; John; Montreal Star; Nationalisme; Nationaliste (Le); Patrie (La); Presse (La)

Dossier: Histoire du meuble - Loubert, Huguette; Ouellet, Richard (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2010)
issued: 2010-24-00/2011-24-00
Keywords: Artisans; Plateau Mont-Royal; Quartiers; Sculpture; Ébénistes

The Long, Angry Summer of ’43: labour Relations in Quebec’s Shipbuilding Industry - Pritchard, James (Labour / Le travail, 2010)
Keywords: Construction navale

Les Livrets de spécimens typographiques de Lovell & Gibson, 1846 et 1847 - Virr, Richard (1870: du journal d'opinion à la presse de masse, la production industrielle de l'information, 2010)
OCLC: 676809390
Keywords: Imprimerie; Lovell; John

The (Spatialized) Hub-and-Spoke Industrial District Model: An Empirical Case Study of Montreal’s Aerospace Sector - Binkovitz, Isaac (Université McGill, 2009)
Keywords: Avionnerie

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

The Life of James Coristine: from Griffintown to the Square Mile - Coristine, Cynthia; Browness, Ian (C. Coristine et I. Browness, 2009)
Keywords: Confection; Fourrure; Marchands; Vêtements

Mainstreaming the Perception and Practice of Ethical Fashion in Montreal - Craven, Ryan John (Université Concordia, 2009)
Keywords: Vêtements

Le développement de la presse depuis la Conquête jusqu'à l'Union - Doyon, Nova (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay; Ludger; Imprimerie; Minerve (La); Montreal Gazette; Montreal Herald

De couturière à Soeur Grise. Le parcours inhabituel de Marie Catherine Demers Dessermon dans le Montréal du XVIIIe siècle - Gousse, Suzanne (Cahiers d'histoire, 2009)
issued: 2009-23-00
Keywords: Communautés religieuses; Confection; Soeurs Grises

L’industrie et l’espace urbain. Étude de l’évolution physique du site de la compagnie Dominion Glass, avenue De Lorimier, à Montréal, 1878-1947 - Lampron, Amélie (Université du Québec à Montréal, 2009)
Keywords: Dominion Glass Company

Ludger Duvernay, le journal La Minerve et la construction identitaire canadienne - Monière, Denis (1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone, 2009)
Keywords: Duvernay; Ludger; Imprimerie; Journalistes; Minerve (La); Rébellions; Société Saint-Jean-Baptiste

1811: De Québec à Montréal, essor de la presse et affirmation d'une parole publique francophone - Doyon, Nova (Petit musée de l'impression et Centre d'histoire de Montréal, 2009)
Keywords: Duvernay; Ludger; Imprimerie; Journalistes; Loyalistes; Minerve (La); Montreal Gazette; Montreal Herald

Angus, du grand capital à l’économie sociale - Nadeau, Gaétan (Fides, 2009)
Keywords: Canadien Pacifique; Chemins de fer; Travail; Usines Angus

Bombardier: A Dream with International Reach, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Bombardier: l'internationalisation d'un rêve, 1942-2008 - Bombardier inc. (Bombardier inc., 2008)
Keywords: Bombardier

Le Québec à l'heure de la Révolution américaine - Boyer, Jean-Pierre (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Du Calvet; Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard; Valentin; Journalistes; Librairie; Mesplet; Fleury

1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal - Ruelland, Jacques G. (Petit musée de l'impression et Centre d'histoire de Montréal, 2008)
Keywords: Du Calvet; Pierre; Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard; Valentin; Journalistes; Librairie; Mesplet; Fleury; Montreal Gazette

L'Académie de Montréal - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Jautard; Valentin; Mesplet; Fleury

Premier imprimeur-libraire à Montréal: Fleury Mesplet (1734-1794), un défenseur des droits humains - de Lagrave, Jean-Paul (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet; Fleury; Montreal Gazette

Fleury Mesplet: le pouvoir de la Presse - de Lagrave, Jean-Paul; Ruelland, Jacques G. (1776: Naissance de l'imprimerie et de la liberté d'expression à Montréal, 2008)
Keywords: Gazette Littéraire de Montréal; Idéologies; Imprimerie; Librairie; Mesplet; Fleury; Montreal Gazette

Design, Presentation Silver and Louis-Victor Fréret (1801-1879) in London and Montreal - Fox, Ross (Material Culture Review / Revue de la culture matérielle, 2008)
Pas dans la période V car il n'est pas à Montréal avant 1867 de ce que nous (JRL) comprenons
issued: 2008-21-00
Keywords: Artisans; Sculpture

Territoire, patrimoine, quartier en développement: le cas de la zone Chabanel au centre-nord de la ville de Montréal - Mariani, Alessandra (Patrimoines: fabrique, usages et réemplois, 2008)
Keywords: Patrimoine; Quartiers

John Molson. Sa vie, son oeuvre - Daignault, Sylvain (Lidec, 2007)
Keywords: Hommes d'affaires; Molson (brasserie)

L'essor du livre illustré au Québec en relation avec les milieux artistiques et éditoriaux français: 1880-1940 - Danaux, Stéphanie (Université de Montréal et Université de Poitiers, 2007)
Keywords: Édition

L’École du meuble de Montréal: au-delà de l’ébénisterie - Dubois, Martin (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Ébénistes; École du meuble

Sir William C. Macdonald. A Biography - Fong, William (McGill-Queen's University Press, 2007)
Keywords: Macdonald College; Macdonald; William C.; Philanthropie; Tabac; Université McGill

Réaménager la tradition - Gaudreau, Valérie (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Ébénistes; École du meuble

Une économie sur ses rails: la contribution du "6000 Saint-Denis" au développement du nord de Montréal - Laplace, Josée (Bulletin de l'Association québécoise pour le patrimoine industriel, 2007)
issued: 2007-21-00
Keywords: Montreal Street Railway Company; Patrimoine; Tramways; Transport en commun

Pointe St. Charles Shop - Leduc, Michael (Michael Leduc, 2007)
Keywords: Chemins de fer; Grand Tronc

Étude de cas. La formation des imprimeurs: L'École des arts graphiques de Montréal. - Leroux, Eric (Histoire du livre et de l'imprimé au Canada, vol. III (1918-1980), 2007)
Keywords: Imprimerie; École des arts graphiques

"Nous ne voulons pas que nos héritiers soient à la merci des tiens": famille, patrimoine et entreprise chez les Rolland, 1880-1980 - Nootens, Thierry (Revue d'histoire de l'Amérique française, 2007)
Number: 1
Keywords: Famille; Patrimoine

Mobilier québécois au MBAM: regards dans le temps et l’espace - Pepall, Rosalind (Continuité, 2007)
issued: 2007-24-00/2008-24-00
Keywords: Musée des Beaux-Arts; Musées

La fabrication culturelle d’un cigare à Montréal au tournant du vingtième siècle - Rudy, Jarrett (Tabac et fumées: regards multidisciplinaires et indisciplinés sur le tabagisme XVe-XXe siècles, 2007)
Keywords: Tabac

Institutions commerciales de Verdun. D'hier à aujourd'hui (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
issued: 2006-24-00
Keywords: Commerce de détail; Confection; Magasins; Quartiers; Quincaillerie; Verdun; Vêtements; Épicerie

Autour de l'enseigne Five Roses: la minoterie Ogilvie, figure de proue du canal de Lachine - Cadorette, Paul-Émile (Bulletin de l'Association québécoise pour le patrimoine industriel, 2006)
issued: 2006-23-00
Keywords: Alimentation; Lachine (canal); Meunerie; Ogilvie Flour Mills

At the End of the Final Line. A Brief History of Aircraft Manufacturing at Canadian Vickers and Canadair - Campbell, Patrick J. (Shoreline, 2006)
Keywords: Avionnerie; Canadair; Canadian Vickers

Aspects of Scottish-Canadian Material Culture: Heart Brooches and Scottish Pottery - Dalgleish, George R. (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Orfèvres; Poterie; Écossais

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath; John; Sucre

Les grands de l’aéronautique: Canadian Vickers, Canadair, Bombardier - Fortier, Rénald (Cap-aux-Diamants, 2006)
issued: 2006-23-00
Keywords: Avionnerie; Bombardier; Canadair; Canadian Vickers

La représentation de l'industrie dans les guides bruxellois et montréalais au tournant du 20e siècle - Kenny, Nicolas (Cahiers de la Fonderie, 2006)
Number: 34
Keywords: Fer et acier; Tourisme

Artisans et industries en milieu rural au Québec avant 1851. L’exemple de l’Île Jésus - Logette, Jérôme (Université du Québec à Montréal, 2006)
Keywords: Artisans; Île Jésus

Hartland de Montarville Molson: man of honour - Molson, Karen (Firefly Books, 2006)
Keywords: Brasserie; Hommes d'affaires; Molson (famille)

La fabrique de pipes à fumer Henderson: inventaire archéologique sur le site Henderson-Dixon, BjFj-135, Montréal, 2005. Arrondissement Ville-Marie - Roy, Christian (Ville de Montréal, 2006)
Keywords: Artisans; Tabac

Habiter, prendre pied, s'établir. Les commerçants et manufacturiers juifs de Montréal, 1918-1930 - Taschereau, Sylvie (Vivre en ville. Bruxelles et Montréal aux XIXe et XXe siècles, 2006)
Keywords: Juifs

A Scottish-born Silversmith in Montreal: Robert Cruikshank - Villeneuve, René (A Kingdom of the Mind: How the Scots Helped Make Canada, 2006)
Keywords: Orfèvres; Écossais

DAVIS, sir MORTIMER BARNETT - Burgess, Joanne (Dictionnaire biographique du Canada, 2005)

Les Forget, luthiers depuis un siècle - Desjardins, Marie (Éditions au Carré, 2005)
Keywords: Artisans; Musique

Les entreprises d'imprimerie et d'édition en Amérique du Nord britannique, 1751-1840 - Hare, John; Wallot, Jean-Pierre (Mens, 2005)
issued: 2005-21-00
Keywords: Imprimerie; Édition

La formation professionnelle des ouvriers des métiers du livre au Québec au XXe siècle - Leroux, Éric (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2005)
issued: 2005-21-00
Keywords: Imprimerie; École des arts graphiques; École technique

Étude de cas. Abraham de Sola, éditeur juif dans le Montréal victorien - Menkins, Richard (Histoire du livre et de l'imprimé au Canada, vol. II (1840-1918), 2005)
Keywords: De Sola; Abraham; Juifs

STEPHEN, GEORGE, 1er baron Mount Stephen - Reford, Alexander (Dictionnaire biographique du Canada, 2005)

LESPÉRANCE, ZOTIQUE - Rouillard, Jacques (Dictionnaire biographique du Canada, 2005)

Histoire de la raffinerie de Petro-Canada à Montréal, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

History of Petro-Canada Montreal refinery, 1955-2005 - Roy, Michel (Petro-Canada, 2005)
Keywords: Pétrole

FABIEN, CLÉOPHAS - Tremblay, Robert (Dictionnaire biographique du Canada, 2005)

RICHARD, MAURICE, dit le Rocket - Vigneault, Michel (Dictionnaire biographique du Canada, 2005)

Les manuels scolaires en Nouvelle-France dans la « Province du Québec » et au Bas-Canada - Aubin, Paul (Histoire du livre et de l'imprimé au Canada, vol. I (des débuts à 1840), 2004)
Keywords: Collège de Montréal; Congrégation de Notre-Dame; Frères Charon; Imprimerie

Enduring Roots: Gibb and Co. and the Nineteenth-Century Tailoring Trade in Montreal - Cariou, Gail (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Fashion and Refuge: The Jane Harris Salon, Montreal, 1941-1961 - Ferrabee Sharman, Lydia (Fashion. A Canadian Perspective, 2004)
Keywords: Vêtements

Un essor laborieux : l'électricité et le monde industriel. Les choix énergétiques des entrepises du canal de Lachine, Montréal, 1880-1920 - Gelly, Alain (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Lachine (canal); Électricité; Énergie hydraulique

La culture urbaine au Canada et les formes de la culture de l'imprimé aux XVIII et XIX siècles - Lamonde, Yvan (Urban History Review / Revue d'histoire urbaine, 2004)
issued: 2004-23-00
Keywords: Imprimerie; Librairie; Édition

A City Transformed: Manufacturing Disctricts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Manufacturing Suburbs. Building Work and Home on the Metropolitan Fringe, 2004)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

The Association of Canadian Couturiers - Palmer, Alexandra (Fashion. A Canadian Perspective, 2004)
Keywords: Confection; Vêtements

Les industries à LaSalle de 1912 à 2002 - Zaïd, Omar; Zitouni, Khadoudja (Histoire Québec, 2004)
Keywords: LaSalle

Daly et Morin, à la recherche du patrimoine industriel de Lachine - Avon, Hélène (Université de Sherbrooke, 2003)
Keywords: Lachine; Patrimoine

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment—despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

La librairie Rolland, 1842-1888 - Déry, Boris (Université du Québec à Montréal, 2003)
Keywords: Librairie

Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Navigation; Énergie hydraulique

Mode, société et apparence: la mode féminine au Québec de 1945 à 2000 - Dulac, Françoise (Université Laval, 2003)
Keywords: Femmes; Vêtements

Le moulin de Pointe-aux-Trembles: survol historique et analyse du parcellaire (BjFi-5), 2001 - Ethnoscop (Ville de Montréal, 2003)
Keywords: Meunerie; Pointe-aux-Trembles; Quartiers

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Lachine (canal); Énergie hydraulique

Syndicats et collectivités dans la gouvernance locale: une recherche exploratoire à Montréal - Klein, Juan-Luis; Fontan, Jean-Marc (Recherches sociographiques, 2003)
issued: 2003-05/2003-08
Keywords: Fédération des travailleurs et travailleuses du Québec (FTQ)

Le grain, la meule et les vents: le métier de meunier en Nouvelle-France - Laperle, Dominique (GID, 2003)
Keywords: Meunerie

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Number: 1
Keywords: Aqueduc; Énergie hydraulique

CATELLI, CARLO ONORATO (Charles-Honoré) - Scardellato, Gabriele (Dictionnaire biographique du Canada, 2003)

L'industrie de la chaussure à Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Travail et syndicalisme: naissance et évolution d'une action sociale, 2002)
Keywords: Artisans; Chaussure

Montréal, 1870-1970: portrait de l’industrie laitière urbaine - Burgess, Joanne (Cap-aux-Diamants, 2002)
issued: 2002-23-00
Keywords: Lait

Making and Breaking Bread in Jewish Montreal, 1920-1940 - Lerner, Eve (Université Concordia, 2002)
Keywords: Alimentation; Boulangerie; Juifs

Tanneurs et tanneries dans le gouvernement de Montréal au XVIIIe siècle - Perrier, Jocelyne (Université de Montréal, 2002)
Keywords: Artisans; Tannerie

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

Les églises: lieux de culte et de culture - Vanlaethem, France (Montréal, la ville aux cent clochers. Regards des Montréalais sur leurs lieux de culte, 2002)
Keywords: Arts sacrés; Patrimoine; Sculpture; Vêtements; Églises

Intermodal Freight Terminals: Locality and Industrial Linkages - McCalla, Robert J.; Slack, Brian; Comtois, Claude (The Canadian Geographer / Le Géographe canadien, 2001)
Number: 3
Keywords: Aéroport; Chemins de fer; Port

A City Transformed: Manufacturing Districts and Suburban Growth in Montreal, 1850-1929 - Lewis, Robert D. (Journal of Historical Geography, 2001)
Number: 1
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Les communautés religieuses et l'édition du manuel scolaire au Québec, 1765-1964 - Aubin, Paul (Groupe de recherche sur l'édition littéraire au Québec, 2001)
Keywords: Communautés religieuses; Enseignants; Édition

La ville, agent catalyseur de développement: le rôle des municipalités dans l’évolution de l’industrie canadienne des véhicules d’incendie, 1945-1965 - Beauvais, Suzanne (Material History Review / Revue d’histoire de la culture matérielle, 2001)
Keywords: Incendies; Pompiers

Ces machines qui chantent… - Bélisle, Jean; Cloutier, Nicole (Continuité, 2001)
issued: 2001-24-00/2002-24-00
Keywords: Musique; Radio

La réorganisation du travail à la raffinerie Shell de Montréal-Est, de 1989 à 1999 - Delorme, Marie-Josée (Université de Montréal, 2001)
Keywords: Montréal-Est; Pétrole; Travail

De génération en génération: la transmission des savoir-faire - Simard, Cyril (Cap-aux-Diamants, 2001)
issued: 2001-21-00
Keywords: Artisans

Résidence et liens de parenté des artisans de Montréal en 1741 - Groulx, François; Gauthier, Jean-Richard (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 2000)
Keywords: Artisans; Arts sacrés; Famille

La saga du technopôle Angus: reconversion productive et reconversion sociale - Klein, Juan-Luis; Fontan, Jean-Marc; Tremblay, Diane-Gabrielle; Bordeleau, Danièle (Les espaces dégradés: contraintes et conquêtes, 2000)
Keywords: Usines Angus

Manufacturing Montreal. The Making of an Industrial Landscape, 1850-1930 - Lewis, Robert D. (John Hopkins University Press, 2000)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Brasseurs, brasseries et activités brassicoles dans la plaine de Montréal, 1788-1852 - Morin, Stéphane (Université du Québec à Montréal, 2000)
Keywords: Brasserie

Les techniques et le commerce de la tannerie à Montréal au XVIIIe siècle - Perrier, Jocelyne (Scientia Canadensis, 2000)
Keywords: Artisans; Marchands; Tannerie

Political Risk in Quebec, Firm Valuation, and Business Relocation Announcements - Lel, Ugur (Université Concordia, 1999)

La dynamique spatiale des activités économiques au Québec. Analyse pour la période 1971-1991 fondée sur un découpage « centre-périphérie » - Polèse, Mario; Roy, Martin (Cahiers de géographie du Québec, 1999)
Number: 118
Keywords: Banlieue; Métropole

Place d'Youville à Montréal: évolution des modes de vie aux abords de la rivière Saint-Pierre entre 1775 et 1838 - Roy, Christian (Archéologiques, 1999)
Number: 13
Keywords: Artisans; Youville (place d')

De la paysanne au tisserand: la production textile dans la région de Montréal au XVIIIe siècle - Roy, Emmanuelle (Regroupement des chercheurs-chercheures en histoire des travailleurs et travailleuses du Québec, 1999)
Keywords: Artisans; Textile; Tissus

De la tête aux pieds…: le Centre national du costume - Bilodeau, Jean-Noël (Cap-aux-Diamants, 1998)
issued: 1998-24-00
Keywords: Costume; Théâtre

BOIVIN, GUILLAUME - Burgess, Joan (Dictionnaire biographique du Canada, 1998)

L'industrie et ses espaces: le Centre-Sud de Montréal, 1872-1980 - Burgess, Joanne (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Centre-sud (quartier); Quartiers

LEGGO, WILLIAM AUGUSTUS - Dansereau, Bernard (Dictionnaire biographique du Canada, 1998)

BERTHIAUME, TREFFLÉ - de Bonville, Jean (Dictionnaire biographique du Canada, 1998)

MACDONALD, sir WILLIAM CHRISTOPHER - Frost, Stanley Brice; Michel (Dictionnaire biographique du Canada, 1998)

L'approche systémique de la gestion et de la prévention des risques d'accident industriel majeur: l'étude d'un cas - Graver, François (Université de Sherbrooke, 1998)

Le discours de l'Association des manufacturiers du Québec (AMQ) sur les stratégies de modernisation sociale de l'entreprise, 1985-1994 - Grignon, Marc (Université du Québec à Montréal, 1998)

BURLAND, JEFFREY HALE - Keating, Peter (Dictionnaire biographique du Canada, 1998)

De la prospérité à l’incertitude: les usines Angus à Rosemont - Laferrière, Suzanne; Vallée, Bernard (Cap-aux-Diamants, 1998)
issued: 1998-22-00
Keywords: Quartiers; Rosemont; Usines Angus

La restructuration de l'industrie - Manzagol, Claude (Montréal 2001. Visages et défis d'une métropole, 1998)

ROSS, JAMES - Regehr, Theodore D. (Dictionnaire biographique du Canada, 1998)

DARLINGTON, WILLIAM - Rouillard, Jacques (Dictionnaire biographique du Canada, 1998)

L'orgue de l'église de la Visitation - Roy, Maurice (Cahiers d'histoire du Sault-au-Récollet, 1998)
issued: 1998-21-00/1998-22-00
Keywords: Artisans; La Visitation (église); Musique; Églises

DRUMMOND, GEORGE EDWARD - Tremblay, Robert (Dictionnaire biographique du Canada, 1998)

Étude socio-professionnelle des familles cordonnières du quartier Saint-Jacques, à Montréal, entre 1861 et 1891 - Bouffard, Luc (Université de Montréal, 1997)
Keywords: Artisans; Chaussure; Quartiers; Saint-Jacques

Paysages industriels en mutation - Burgess, Joanne (Écomusée du fier monde, 1997)
Keywords: Centre-sud (quartier); Patrimoine; Paysages; Quartiers; Saint-Jacques; Sainte-Marie

Montréal capitale du gramophone: l’aventure d’Émile Berliner - Cloutier, Nicole (Cap-aux-Diamants, 1997)
issued: 1997-24-00
Keywords: Chanson; Gramophone; Musique

Les boulangers à Montréal, de la fondation à 1750. Étude d'histoire socio-économique - Lamonde, Robert (Université de Montréal, 1997)
Keywords: Alimentation; Boulangerie

Familles de charpentiers et de menuisiers à Montréal au XVIIIe siècle: alliances matrimoniales et reproduction sociale - Langlois, France-Isabelle (Université de Montréal, 1997)
Keywords: Charpentiers; Famille; Mariage; Menuisiers

Les familles de tisserands de la plaine de Montréal au XVIIIe siècle: étude socioprofessionnelle - Roy, Emmanuelle (Université de Montréal, 1997)
Keywords: Artisans; Textile; Tissus

Montréal... l'histoire oubliée (Histoire Québec, 1996)
Number: 1
Keywords: Arts sacrés; Leduc; Ozias; Musées; Peinture; Églises

Sur l'internationalisation de l'espace économique métropolitain de Montréal: éléments théoriques et portrait de l'évolution récente des statistiques régionales des industries manufacturières exportatrices: (1974-1993) - Arteau, Richard (Université du Québec à Montréal, 1996)
Keywords: Métropole

La fabrication des timbres-poste canadiens et des billets de banque à Montréal de 1871 à 1889: la British American Bank Note - Caron, Normand (Histoire Québec, 1996)
Number: 1
Keywords: Banques; Imprimerie; Poste

L'échelle et le serpent ou comment se faisait Le Devoir - Francoeur, Jean (Le Devoir: un journal indépendant, 1910-1995, 1996)
Keywords: Devoir (Le)

Les meuniers dans la région de Montréal à l'époque de la Nouvelle-France (1642-1760): alliances matrimoniales et reproduction sociale - Laperle, Dominique (Université de Montréal, 1996)
Keywords: Famille; Mariage; Meunerie

Arsène Pigeon (1844-1908) - Prévost, Robert (Cahiers d'histoire du Sault-au-Récollet, 1996)
issued: 1996-21-00
Keywords: Artisans; Logement; Pigeon (famille)

Fouilles archéologiques, 1994. Site Logan-Munn, BiFj-25 et BiFj-4. Angle des rues McGill et de la Commune, Vieux-Montréal. Volume 1: Rapport - Ethnoscop (Société immobilière du patrimoine architectural de Montréal (SIMPA), Ville de Montréal et Ministère de la Culture et des Communications, 1995)
Keywords: Construction navale; Hôpital Général

Structure et effectifs des métiers du fer à Montréal avant 1765 - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1995)
issued: 1995-22-00
Keywords: Artisans; Fer et acier

Moulins et meuniers du Bas-Lachine, 1667-1890 - Gravel, Denis (Septentrion, 1995)
Keywords: Arrondissements; LaSalle; Lachine; Meunerie

Canadair: cinquante ans d'histoire - Pickler, Ron; Milberry, Larry (Canav Books, 1995)
Translators: _:n58086
Keywords: Avionnerie; Bombardier; Canadair

Canadair: the first 50 years - Pickler, Ron; Milberry, Larry (Canav Books, 1995)
Keywords: Avionnerie; Bombardier; Canadair

La structuration sociale de l'activité stratégique: le cas Irving Samuel/Jean-Claude Poitras - Rouleau, Linda (Université Concordia, 1995)
Keywords: Artisans; Confection; Vêtements

Jewish labour and business in the dressmakers'strikes of tje 1930: A clash of cultures in a confined space - Tulchinsky, Gerald (Espace et culture, 1995)
Keywords: Grèves; Juifs; Vêtements

CLENDINNENG, WILLIAM - Bischoff, Peter; Tremblay, Robert (Dictionnaire biographique du Canada, 1994)

"Our Prosperity Rests Upon Manufactures": Industry in the Central Canadian Urban System, 1871 - Bloomfield, G.T.; Bloomfield, Elizabeth (Urban History Review / Revue d'histoire urbaine, 1994)
Number: 2

La culture matérielle des Canadiens au XVIIIe siècle: analyse du niveau de vie des artisans du fer - Bouchard, Dominique (Revue d'histoire de l'Amérique française, 1994)
Number: 4
Keywords: Artisans; Fer et acier

Les changements technologiques et le développement du sud-ouest de Montréal - Boucley, Charles E. (Université de Montréal, 1994)

DRUMMOND, sir GEORGE ALEXANDER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

OGILVIE, ALEXANDER WALKER - Brassard, Michèle; Hamelin, Jean (Dictionnaire biographique du Canada, 1994)

DAWES, JAMES PAWLEY - Burr, Gordon (Dictionnaire biographique du Canada, 1994)

L'État, les patrons, les propriétaires et les marchands: l'évolution des fabriques de transformation laitière au Québec, 1870-1914 - Caux, Rachel (Université du Québec à Montréal, 1994)
Keywords: Lait

GRENIER, JACQUES - Desrochers, Luc (Dictionnaire biographique du Canada, 1994)

COCHRANE, MATTHEW HENRY - Ferland, Jacques (Dictionnaire biographique du Canada, 1994)

GAULT, ANDREW FREDERICK - Hinton, Michael (Dictionnaire biographique du Canada, 1994)

SHEARER, JAMES - McNally, Larry S. (Dictionnaire biographique du Canada, 1994)

LE MOYNE DE MARTIGNY, VITE-ADÉLARD - Paré, Jean-Pierre (Dictionnaire biographique du Canada, 1994)

LAVALLÉE, AUGUSTIN - Picard, Guylaine (Dictionnaire biographique du Canada, 1994)

ROYAL, JOSEPH - Silver, A. I. (Dictionnaire biographique du Canada, 1994)

Mapping the Changes: the Spatial Development of Industrial Montreal, 1861-1929 - Slack, Brian; Meana, Lourdes; Langford, Martha; Thornton, Patricia (Urban History Review / Revue d'histoire urbaine, 1994)
Number: 2
Keywords: Alimentation; Cartes et plans

Sauvetage archéologique sur le site du chantier naval Munn, BiFj-25, 1993 - Société d'archéomatique Chronogramme-Lauverbec (Société immobilière du patrimoine architectural de Montréal (SIMPA), 1993)
Keywords: Construction navale

Taking the Bitter with the Sweet: Sugar Refiners and the Canadian Regulatory State, 1904-20 - Cruikshank, Ken (Canadian Historical Review, 1993)
Number: 3
Keywords: Sucre

La région de Montréal face au déclin des dépenses militaires - Bélanger, Yves (Cahiers de géographie du Québec, 1993)
Number: 102
Keywords: Armée

Les industries manufacturières de haute technologie de la région de Montréal: racines séculaires ou silicon island? - Boisvert, Éric (Université du Québec à Montréal, 1993)

La fabrication des caractères d’imprimerie à Montréal au milieu du XIXe siècle - Dansereau, Bernard (Revue d'histoire de l'Amérique française, 1993)
Number: 1
Keywords: Imprimerie

Étude historique et analyse patrimoniale des usines Angus - Des Rochers, Jacques (s.n., 1993)
Keywords: Chemins de fer; Usines Angus

The Nature of Cooperation between Pharmaceutical Firms in the Greater Montreal Area: A Descriptive Study - Trudeau, Caroline (Université Concordia, 1993)
Keywords: Produits pharmaceutiques

Tensions et solidarité: la formation des traditions syndicales chez les mouleurs de Montréal, Hamilton et Toronto, 1851 à 1893 - Bischoff, Peter (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1992)
issued: 1992-24-00
Keywords: Fer et acier; Mouleurs

L'industrie manufacturière de haute technologie dans la région de Montréal: tendances spatiales et facteurs de localisation - Boisvert, Éric (Montréal: tableaux d'un espace en transformation, 1992)

Bombardier: A Dream with International Reach, 1942-1992 - Bombardier inc. (Bombardier inc., 1992)
Keywords: Bombardier

Bombardier: l'internationalisation d'un rêve, 1942-1992 - Bombardier inc. (Bombardier inc., 1992)
Keywords: Bombardier

Le district de la Fourrure au centre-ville de Montréal - Bouchard, Céline (Université de Montréal, 1992)
Keywords: Centre-ville; Fourrure; Quartiers

Le niveau de vie des artisans du fer à Montréal et à Québec entre 1730 et 1780 - Bouchard, Dominique (Université de Montréal, 1992)
Keywords: Artisans; Fer et acier

L'avènement de la linotype: le cas de Montréal à la fin du XIXe siècle - Dansereau, Bernard (VLB, 1992)
Keywords: Imprimerie

Vivre en Canada - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

"Les p'tites bières" - Germain, Robert (Cap-aux-Diamants, 1992)
issued: 1992-24-00
Keywords: Alcool; Brasserie

Le Pont Victoria. Le lien vital - Kennell, Elizabeth H. (Montréal, une histoire à suivre, 1992)
Translators: _:n34924
Keywords: Ponts; Victoria (pont)

Victoria Bridge. The Vital Link - Kennell, Elizabeth H. (Montreal, a History to Treasure, 1992)
Translators: _:n34943
Keywords: Ponts; Victoria (pont)

Bien plus qu'un almanach! La librairie Beauchemin - Landry, François (Cap-aux-Diamants, 1992)
issued: 1992-24-00
Keywords: Beauchemin (librairie); Librairie; Reliure

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

L'industrie textile primaire au Canada histoire et patrimoine - McCullough, Alan Bruce (Lieux historiques nationaux (service canadien des parcs), 1992)
Keywords: Patrimoine; Textile

Randolph Hersey and the Montréal Nail Industry, 1852-1903 - McNally, Larry (Material History Review / Revue d’histoire de la culture matérielle, 1992)
issued: 1992-23-00

Technical Advance and Stagnation: the Case of Nail Production in Nineteenth-Century Montréal - McNally, Larry (Material History Review / Revue d’histoire de la culture matérielle, 1992)
issued: 1992-23-00

The Changing Face of Fashion in Montreal, 1885-1905: New Markets, Improved Taste and the Move to Mass Production - Payton-Tayler, Evlyn (Université Concordia, 1992)
Keywords: Vêtements

Du forgeron au machiniste: l'impact social de la mécanisation des opérations d'usinage dans l'industrie de la métallurgie à Montréal de 1815 à 1860 - Tremblay, Robert (Université du Québec à Montréal, 1992)

Struggling on Many Fronts: Gender, Work and Unionization - Aguiar, Luis (McMaster University, 1991)
Keywords: Textile; Vêtements

La raffinerie de sucre Redpath: 1720, rue du Canal, Montréal. Vol. 1. Étude historique et architecturale; Vol. 2. Catalogue des bâtiments; Vol. 3. Synthèse - Bélisle, Jean (Ministère des affaires culturelles et Ville de Montréal, Service de l'habitation et du développement urbain, Module gestion du développement, 1991)
Keywords: Redpath Sugar

Moulin à vent - Bélisle, Jean (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Meunerie; Patrimoine; Pointe-aux-Trembles

Moulin à vent - Bélisle, Jean (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: LaSalle; Meunerie; Patrimoine

Planification de la production à la brasserie Molson-O'Keefe - Bourbonnais, Jacques (Université Concordia, 1991)
Keywords: Brasserie; Molson (brasserie)

Bâtisse L.-O . Grothé - Cavanagh, Brian; Lachapelle, Jacques (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Patrimoine; Tabac

Les chantiers navals du canal Lachine - Corbel, Nadine H. J. (Université Concordia, 1991)
Keywords: Construction navale; Navigation

The Spread of Rural Industry in Lower Canada, 1831-1851 - Courville, Serge; Robert, Jean-Claude; Séguin, Normand (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1991)
Number: 1
Keywords: Recensements

Redpath. The History of a Sugar House - Feltoe, Richard (Natural Heritage/Natural History, 1991)
Keywords: Redpath Sugar; Sucre

The Development of an Early Suburban Industrial District: The Montreal Ward of Saint-Ann, 1851-71 - Lewis, Robert D. (Urban History Review / Revue d'histoire urbaine, 1991)
Number: 3
Keywords: Quartiers; Sainte-Anne

Montreal Engine Foundries and their Contribution to Central Canadian Technical Development - Mc Nally, Larry Stewart (Université Carleton, 1991)
Keywords: Fer et acier

Moulin banal de Pointe-Claire - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Meunerie; Patrimoine; Pointe-Claire

Sondages exploratoires et surveillance archéologique sur le site du moulin Fleming, LaSalle - Savard, Mario (Groupe de recherches en histoire du Québec rural, 1991)
Keywords: Arrondissements; LaSalle; Meunerie

Les Sicard - Bertrand, Jacques (Cahiers d'histoire du Sault-au-Récollet, 1990)
issued: 1990-23-00
Keywords: Meunerie; Rivière-des-Prairies

Histoire de l'orgue du Grand Séminaire - Bigras, Yvon (Le Grand Séminaire de Montréal de 1840 à 1990: 150 années au service de la formation des prêtres, 1990)
Keywords: Grand séminaire; Musique; Sulpiciens

ROBERTSON, JAMES - Bischoff, Peter; Tremblay, Robert (Dictionnaire biographique du Canada, 1990)

Chronique de l'industrie de la chaussure dans Hochelaga-Maisonneuve - Carrera, Jose David (D'une trac à l'autre, 1990)
Number: 1
Keywords: Artisans; Chaussure; Hochelaga (quartier); Maisonneuve; Quartiers; Travail

McGARVEY, OWEN - Collard, Elizabeth (Dictionnaire biographique du Canada, 1990)

MACPHERSON, sir DAVID LEWIS - Cruikshank, Ken (Dictionnaire biographique du Canada, 1990)

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

KERRY, JOHN - Ferland, Jacques (Dictionnaire biographique du Canada, 1990)

Intervention gouvernementale et industrie aéronautique: l'exemple canadien, 1920-1965 - Fortier, Rénald (Université Laval, 1990)
Keywords: Avionnerie

HENDERY, ROBERT - Fox, Ross (Dictionnaire biographique du Canada, 1990)

Le grand orgue Guilbault-Thérien de la chapelle du Grand Séminaire de Montréal - Grandmaison, Pierre (Le Grand Séminaire de Montréal de 1840 à 1990: 150 années au service de la formation des prêtres, 1990)
Keywords: Grand séminaire; Sulpiciens

Monographie du Moulin Fleming à Ville de LaSalle - Gravel, Denis (Société historique Cavelier-de-LaSalle, 1990)
Keywords: Arrondissements; LaSalle; Meunerie

MACDONALD (Sandfield), DONALD ALEXANDER - Hodgins, Bruce W.; White, Paul W. (Dictionnaire biographique du Canada, 1990)

ROSE, GEORGE MACLEAN - Hulse, Elizabeth (Dictionnaire biographique du Canada, 1990)

WILSON, JAMES CROCKET - Laurin, Serge (Dictionnaire biographique du Canada, 1990)

OGILVIE, WILLIAM WATSON - Levine, Allan (Dictionnaire biographique du Canada, 1990)

VIAU, CHARLES-THÉODORE - Linteau, Paul-André (Dictionnaire biographique du Canada, 1990)

McDOUGALL, JOHN - Milot, Maurice (Dictionnaire biographique du Canada, 1990)

LOVELL, JOHN - Parker, George L. (Dictionnaire biographique du Canada, 1990)

HUDON, VICTOR - Rudin, Ronald E. (Dictionnaire biographique du Canada, 1990)

DAVIS, SAMUEL - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1990)

SHOREY, HOLLIS - Tulchinsky, Gérald Jacob Joseph (Dictionnaire biographique du Canada, 1990)

CANTIN, AUGUSTIN - Tulchinsky, Gérald Joseph Jacob (Dictionnaire biographique du Canada, 1990)

DICKINSON, MOSS KENT - Turner, Larry (Dictionnaire biographique du Canada, 1990)

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

Le potentiel archéologique du site du moulin Fleming, LaSalle - Savard, Mario; Côté, Robert (Groupe de recherches en histoire du Québec rural, 1989)
Keywords: Arrondissements; LaSalle; Meunerie

Les laboratoires Nordic. L'histoire d'une réussite - Gosselin, Léo (Boréal, 1989)
Keywords: Laboratoires Nordic; Pharmacie; Produits pharmaceutiques

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Cahiers de géographie du Québec, 1989)
Number: 90
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

Power: The Pratt & Whitney Canada Story - Sullivan, Kenneth H.; Milberry, Larry (CANAV Books, 1989)
Keywords: Avionnerie; Pratt & Whitney

Propulsion. L'histoire de Pratt & Whitney Canada - Sullivan, Kenneth H.; Milberry, Larry (CANAV Books, 1989)
Keywords: Avionnerie; Pratt & Whitney

A Merchant of Death in the Peaceable Kingdom: Canadian Vickers, 1911-1927 - Taylor, Graham D. (Canadian Papers in Business History, Volume I, 1989)
Keywords: Canadian Vickers; Construction navale

DULONGPRÉ, LOUIS - Bazin, Jules (Dictionnaire biographique du Canada, 1988)

John Lovell (1810-93): Montreal Music Printer and Publisher - Bryce, Maria Calderisi (Musical Canada: Words and Music Honouring Helmut Kallman, 1988)
Keywords: Imprimerie; Lovell; John; Musique; Édition

BROWN, JAMES - Chéné, Lucie (Dictionnaire biographique du Canada, 1988)

BEAUVAIS, Saint-James, RENÉ - Cloutier, Nicole (Dictionnaire biographique du Canada, 1988)

GRIFFITH, JOHN - Collard, Elizabeth (Dictionnaire biographique du Canada, 1988)

PÉPIN, JOSEPH - Gauthier, Raymonde (Dictionnaire biographique du Canada, 1988)

Analyse idéologique de l’Association professionnelle des industriels (1956-1966) - Leblanc, Louise (Université de Montréal, 1988)

BULL, GEORGE PERKINS - Senior, Hereward (Dictionnaire biographique du Canada, 1988)

DELORME, CHARLES-SIMON - Tremblay, Robert (Dictionnaire biographique du Canada, 1988)

FORSYTH, JOHN - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1988)

Historique des Éditions Fides - Bertrand, Guy-Marie (Fides, 1987)
Keywords: Fides; Édition

GIBB, BENAIAH - Burgess, Joanne (Dictionnaire biographique du Canada, 1987)

DRUMMOND, ROBERT - Bush, Edward F. (Dictionnaire biographique du Canada, 1987)

QUÉVILLON, LOUIS - Cloutier, Nicole (Dictionnaire biographique du Canada, 1987)

Canadian Railways as Manufacturers, 1850-1880 - Craven, Paul; Traves, Tom (Perspectives on Canadian Economic History, 1987)
Keywords: Chemins de fer; Grand Tronc

DUVAL, CHARLES - Derome, Robert (Dictionnaire biographique du Canada, 1987)

ROUSSEAU, DOMINIQUE - Derome, Robert (Dictionnaire biographique du Canada, 1987)

MARION, SALOMON - Derome, Robert; Ménard, José (Dictionnaire biographique du Canada, 1987)

A Study of the Point St. Charles Shops of the Grand Trunk Railway in Montreal, 1880-1917 - Hoskins, Ralph F. H. (Université McGill, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

An Analysis of the Payrolls of the Point St. Charles Shops of the Grand Trunk Railway - Hoskins, Ralph F. H. (Université McGill, Département de géographie, 1987)
Keywords: Chemins de fer; Grand Tronc; Pointe-Saint-Charles; Quartiers

McCORD, THOMAS - Kyte Senior, Elionor (Dictionnaire biographique du Canada, 1987)

GRAY, JOHN - Miller, Carman (Dictionnaire biographique du Canada, 1987)

The Process of Hydraulic Industrialization on the Lachine Canal, 1840-1880: Origins, Rise and Fall - Willis, John (Environnement Canada, Service canadien des Parcs, 1987)
Keywords: Lachine (canal); Énergie hydraulique

JOSEPH, HENRY - Wolff, Annette R. (Dictionnaire biographique du Canada, 1987)

Extrait de la vie domestique d'une famille de cultivateur et d'artisan du faubourg Saint-Louis, 1745-1825, site Viger, Montréal - Laliberté, Monique (Société d'archéologie et de numismatique de Montréal, 1986)
Keywords: Artisans; Famille; Faubourgs; Quartiers; Saint-Louis

The Montreal Garment Industry, 1871-1901 - Payette-Daoust, Michelle (Université McGill, 1986)
Keywords: Confection

For the Benefit of the Master: the Montreal Needle Trades During the Transition, 1820-1842 - Poutanen, Mary Anne (Université McGill, 1986)
Keywords: Apprentissage; Confection; Femmes

La position concurentielle de l'industrie manufacturière montréalaise, 1971-1981-1991 - Thibodeau, J.-C.; Martineau, Yves; Pontbriand, M.-C. (INRS-Urbanisation, 1986)

Life Cycles and Strategy of a Canadian Company: Dominion Textile, 1873-1983 - Austin, Barbara J. (Université Concordia, 1985)
Keywords: Textile

McKAY, THOMAS - Bush, E.F. (Dictionnaire biographique du Canada, 1985)

Global Mission: the Story of Alcan - Campbell, Duncan C. (Ontario Publishing, 1985)
issued: 1985/1990
Keywords: Alcan; Aluminium

Mission mondiale. Histoire d'Alcan - Campbell, Duncan C. (divers éditeurs, 1985)
issued: 1980/1990
Keywords: Alcan; Aluminium

De fil en aiguille: chronique ouvrière d'une filature de coton à Hochelaga en 1880 - Charbonneau, Réjean (Société Saint-Jean Baptiste, 1985)
Keywords: Hochelaga (quartier); Quartiers; Textile; Travail

BAIRD, EDMOND - Collard, Elizabeth (Dictionnaire biographique du Canada, 1985)

KIMBER, TIMOTHÉE - de Lorimier, Michel (Dictionnaire biographique du Canada, 1985)

MORAND, PAUL - Derome, Robert; Morgan, Norman (Dictionnaire biographique du Canada, 1985)

CLEMO, EBENEZER - Edwards, Mary Jane (Dictionnaire biographique du Canada, 1985)

ROY, JOSEPH - Galarneau, France (Dictionnaire biographique du Canada, 1985)

ROTTERMUND, ÉDOUARD-SYLVESTRE DE, comte de ROTTERMUND - Jarrell, Richard A. (Dictionnaire biographique du Canada, 1985)

FASSIO, GEROME - Karel, David (Dictionnaire biographique du Canada, 1985)

HUSTON, JAMES - Lemire, Maurcie (Dictionnaire biographique du Canada, 1985)

Impact of Mechanization in the Glass Container Industry: the Dominion Glass Company of Montreal, a Case Study - Miller, George L.; Pacey, Antony (Historical Archaeology, 1985)
Number: 1
Keywords: Dominion Glass Company

La boulangerie à Montréal sous le régime français - Montbriand, Monique (Cahier de la Société historique de Montréal, 1985)
Number: 1
Keywords: Boulangerie

CRANE, SAMUEL - Pietersma, Harry (Dictionnaire biographique du Canada, 1985)

J.-Armand Bombardier - Precious, Carole (Lidec, 1985)
Translators: _:n48899
Keywords: Bombardier

The Publishers Press of Montreal - Spadoni, Carl (Cahiers de la Société bibliographique du Canada / Papers of the Bibliographical Society of Canada, 1985)
Keywords: Édition

L'histoire d'une communauté ouvrière et d'une transformation d'entreprise en coopérative de travailleurs: l'Imprimerie coopérative Harpel - Vincent, Paul (École des hautes études commerciales, 1985)
Keywords: Imprimerie; Imprimerie coopérative Harpel

Brève histoire de notre imprimerie provinciale - Déziel, Julien (Chroniques et Documents, 1984)
Number: 2
Keywords: Communautés religieuses; Franciscains; Imprimerie

Les éditions Edouard Garand et la culture populaire québécoise - Gagnon, Claude-Marie (Voix et Images, 1984)
Number: 1
Keywords: Édition

Management Relations in a Multinational Enterprise: The Case of Canadian Industries Limited, 1928-1948 - Taylor, Graham D. (Essays in Canadian Business History, 1984)
Keywords: Canadian Industries Limited

L'évolution récente de l'industrie manufacturière à Montréal - Manzagol, Claude (Cahiers de géographie du Québec, 1983)
Number: 71

FISHER, DUNCAN - Armstrong, Frederick H. (Dictionnaire biographique du Canada, 1983)

ROLLO, JAMES - Collard, Elizabeth (Dictionnaire biographique du Canada, 1983)

ARNOLDI, MICHAEL - Derome, Robert (Dictionnaire biographique du Canada, 1983)

CRUICKSHANK, ROBERT - Derome, Robert (Dictionnaire biographique du Canada, 1983)

ROY, NARSISE - Derome, Robert; Ménard, José (Dictionnaire biographique du Canada, 1983)

HUGUET, Latour, PIERRE - Derome, Robert; Morgan, Norman (Dictionnaire biographique du Canada, 1983)

VIGER, DENIS - Désy, Louise (Dictionnaire biographique du Canada, 1983)

MÉZIÈRE, HENRY-ANTOINE - Galarneau, Claude (Dictionnaire biographique du Canada, 1983)

EDWARDS, EDWARD - Hare, John E. (Dictionnaire biographique du Canada, 1983)

Dundee-Built Locomotive in Canada's First Railways - Lavallée, Omer S. A. (Railroad History, 1983)
issued: 1983-23-00
Keywords: Chemins de fer

The Relationship between Transportation and Water Power on the Lachine Canal in the Nineteenth Century - McNally, Larry (Critical Issues in the History of Canadian Science, Technology and Medicine, 1983)
Keywords: Lachine (canal); Énergie hydraulique

PÉRINAULT, JOSEPH - Ouellet, Fernand (Dictionnaire biographique du Canada, 1983)

Imprimerie et diffusion de l'imprimé à Montréal, 1776-1830 - Buono, Yolande (Documentation et bibliothèques, 1982)
Number: 1
Keywords: Imprimerie

BOURNE, ADOLPHUS - Allodi, Mary (Dictionnaire biographique du Canada, 1982)

De la voile à la vapeur: la construction des navires dans les environs de Québec et de Montréal / From Sail to Steam (...) - Baker, Victoria A.; Dutton, Diana (Musée Marsil de Saint-Lambert / Marsil Museum of Saint-Lambert, 1982)
Keywords: Construction navale; Navigation

Shop Angus, 1904-1982: ça va faire du train! - Boucher, Claude; Primeau, Jacques; Thibeault, Marc (Comité de logement Rosemont, 1982)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

TRUDEAU, ROMUALD - Chabot, Richard (Dictionnaire biographique du Canada, 1982)

ARMSTRONG, GEORGE - Collard, Elizabeth (Dictionnaire biographique du Canada, 1982)

LAVIGNE, AZARIE - Collard, Elizabeth (Dictionnaire biographique du Canada, 1982)

Vision in Steel, 1882-1982: One Hundred Years of Growth. Dominion Bridge to AMCA International - Dunwell, Steve (AMCA International, 1982)
Keywords: Dominion Bridge; Fer et acier

Le rôle des déterminismes sociaux dans le développement des forces productives de l'industrie textile du Canada, 1870 à 1910 - Ferland, Jacques (Université McGill, 1982)
Keywords: Textile

HIBBARD, ASHLEY - Gervais, Gaétan (Dictionnaire biographique du Canada, 1982)

RODIER, CHARLES-SÉRAPHIN - Linteau, Paul-André (Dictionnaire biographique du Canada, 1982)

ROLLAND, JEAN-BAPTISTE - Linteau, Paul-André (Dictionnaire biographique du Canada, 1982)

LEGGE, CHARLES - McNally, Larry S. (Dictionnaire biographique du Canada, 1982)

Water Power on the Lachine Canal 1846-1900 - Mcnally, Larry S. (Parcs Canada, 1982)
Keywords: Lachine (canal); Énergie hydraulique

BOURGEAU, VICTOR - Noppen, Luc (Dictionnaire biographique du Canada, 1982)

COUPER, WILLIAM - Paradis, Rodolphe O. (Dictionnaire biographique du Canada, 1982)

DAVID, FERDINAND - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1982)

MUNRO, HECTOR - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1982)

PATTERSON, WILLIAM JEFFREY - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1982)

BEAUCHEMIN, CHARLES-ODILON - Roy, Jean-Louis (Dictionnaire biographique du Canada, 1982)

DUNCAN, JAMES D - Todd, Patricia A. (Dictionnaire biographique du Canada, 1982)

DORWIN, JEDEDIAH HUBBELL (Dictionnaire biographique du Canada, 1982)

BRUSH, GEORGE - Tulchinsky, Gérald Jacob Joseph (Dictionnaire biographique du Canada, 1982)

La petite entreprise au Canada au XIXe siècle: le cas de l'industrie de la chaussure à Montréal - Burgess, Joanne (Petite entreprise et croissance industrielle dans le monde aux XIXe et XXe siècles, 1981)
Keywords: Artisans; Chaussure

Montréal, 1840-1870: le passage de l'artisanat à la fabrique - Burgess, Joanne (Les métiers du cuir, 1981)
Keywords: Artisans; Chaussure

Analyse de l'expansion récente du secteur manufacturier sur la Rive-Sud de Montréal - Lareau, Jacques (Université de Montréal, 1981)
Keywords: Banlieue

Drummond McCall a cent ans, 1881-1981 - Meyer, John (Drummond McCall, 1981)
Keywords: Drummond McCall; Fer et acier

The Story of Drummond McCall, 1881-1981 - Meyer, John (Drummond McCall, 1981)
Keywords: Drummond McCall; Fer et acier

Les meuniers dans la seigneurie de l'Ile de Montréal au XVIIIe siècle - Objois, Catherine (Université de Montréal, 1981)
Keywords: Meunerie; Seigneurie

L'industrialisation à Hochelaga-Maisonneuve, 1900-1930 - Bouchard, Daniel (L'Atelier d'histoire Hochelaga-Maisonneuve, 1980)
Keywords: Hochelaga (quartier); Maisonneuve (quartier); Quartiers

Imprimerie et diffusion de l'imprimé à Montréal de 1776 à 1820 - Buono, Yolande (Université de Montréal, 1980)
Keywords: Imprimerie

DELEZENNE, IGNACE-FRANÇOIS - Derome, Robert (Dictionnaire biographique du Canada, 1980)

VARIN, La Pistole, JACQUES - Derome, Robert (Dictionnaire biographique du Canada, 1980)

MESPLET, FLEURY - Galarneau, Claude (Dictionnaire biographique du Canada, 1980)

ROY, LOUIS - Hare, John E. (Dictionnaire biographique du Canada, 1980)

SOUSTE, ANDRÉ - Lachance, André (Dictionnaire biographique du Canada, 1980)

HUPPÉ, Lagroix, JOSEPH - Moogk, Peter N. (Dictionnaire biographique du Canada, 1980)

TESSIER, Lavigne, PAUL - Moogk, Peter N. (Dictionnaire biographique du Canada, 1980)

Les ouvrières à domicile et l'industrie de la robe à Montréal - Morissette, Diane (Université de Montréal, 1980)
Keywords: Confection; Vêtements

Le chauffage domestique au Canada: des origines à l'industrialisation - Moussette, Marcel (Université Laval, 1980)
Keywords: Bois de chauffage

CIRIER, ANTOINE - Porter, John R. (Dictionnaire biographique du Canada, 1980)

FOUREUR, Champagne, LOUIS - Porter, John R. (Dictionnaire biographique du Canada, 1980)

BARSALOU, JEAN-BAPTISTE - Tremblay, Yves-Jean (Dictionnaire biographique du Canada, 1980)

The Ancestor of Quebec's Craft Unions: the Montreal Shoemakers' Protest of 1729 - Moogk, Peter N. (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1978)
Number: 1
Keywords: Artisans; Chaussure; Grèves

Fleury Mesplet, Printer to the Congress in Montreal - Thériault, Michel (Forces, 1978)
Keywords: Imprimerie; Mesplet; Fleury

L'industrie de la chaussure à Montréal: 1840-1870 - Le passage de l'artisanat à la fabrique - Burgess, Joanne (Revue d'histoire de l'Amérique française, 1977)
Number: 2
Keywords: Artisans; Chaussure

L'industrie de la chaussure à Montréal 1840-1870: de l'artisanat à la fabrique - Burgess, Joanne (Université du Québec à Montréal, 1977)
Keywords: Artisans; Chaussure

HILTON, JOHN - Collard, Elizabeth (Dictionnaire biographique du Canada, 1977)

MOLSON, THOMAS - Dubuc, Alfred (Dictionnaire biographique du Canada, 1977)

Angus Shops of the Canadian Pacific Railway - Elson, Harvey W. (Canadian Rail, 1977)
Keywords: Canadien Pacifique; Chemins de fer; Usines Angus

BELL, JOSHUA - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1977)

BOYER, LOUIS - Robert, Jean-Claude (Dictionnaire biographique du Canada, 1977)

PERRAULT, LOUIS - Roy, Jean-Louis (Dictionnaire biographique du Canada, 1977)

DOW, WILLIAM - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1977)

HARRIS, FREDERICK WARREN - Tulchinsky, Gerald J.J. (Dictionnaire biographique du Canada, 1977)

REDPATH, JOHN - Tulchinsky, Gérald Jacob Joseph (Dictionnaire biographique du Canada, 1977)

WATSON, WILLIAM - Tulchinsky, Gérald Jacob Joseph (Dictionnaire biographique du Canada, 1977)

L'industrie à Montréal en 1871 - Martel, Eve (Université du Québec à Montréal, 1976)

Centrality and Locational Change: Printing, Publishing and Clothing in Montreal and Toronto - Steed, Guy P. F. (Economic Geography, 1976)
Number: 3
Keywords: Confection; Imprimerie; Publicité; Édition

Standardization, Scale, Incubation and Inertia: Montreal and Toronto Clothing Industries - Steed, Guy P. F. (The Canadian Geographer / Le Géographe canadien, 1976)
issued: 1976-23-00
Keywords: Confection; Vêtements

Industrial Type and Dependence on the Montreal Economy - Gilmour, James M.; Murricane, Kenneth (Cahiers de géographie du Québec, 1975)
Number: 47

Évolution de l'implantation manufacturière dans la région de Montréal de 1962 à 1972 - Martineau, Yvon (Université de Montréal, 1975)

Inter-Urban Industrial Linkages in Montreal's Hinterland - Murricane, Kenneth (Université McGill, 1975)

Bilan, perspectives et éléments de stratégie. Secteur des industries manufacturières - Jouandet-Bernadat, Roland (L'Actualité économique, 1974)
issued: 1974-07/1974-09

Montreal Cabinetmakers and Chairmakers, 1800-1850: A Check List - Collard, Elizabeth (Antiques, 1974)
issued: 1974-01/1974-06
Keywords: Ébénistes

CHEVAL, dit Saint-Jacques, Chevalier, JACQUES-JOSEPH - Auger, Roland-J. (Dictionnaire biographique du Canada, 1974)

GADOIS, Mauger, JACQUES - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

JOURDAIN, Labrosse, PAUL-RAYMOND - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

PARADIS, ROLAND - Cauchon, Michel; Juneau, André (Dictionnaire biographique du Canada, 1974)

SAINT-PÈRE, AGATHE DE - Doyon-Ferland, Madeleine (Dictionnaire biographique du Canada, 1974)

Fibracan Inc.: History, Analysis of Current Business, Long Range Plan, 1974-1979 - Garrett, M.; Kerry, D.; Thompson, M. (Université Concordia, 1974)

CORON, CHARLES-FRANÇOIS - Kallmann, Helmut (Dictionnaire biographique du Canada, 1974)

MOREAU, EDME - Moogk, Peter N. (Dictionnaire biographique du Canada, 1974)

Analyse économique du secteur manufacturier de la zone métropolitaine de Montréal - Bisson, Jean-Marc (Université de Montréal, 1973)

The Spatial Linkages of Manufacturing in Montreal and its Surroundings - Brooks, Stanley; Gilmour, James M.; Murricane, Kenneth (Cahiers de géographie du Québec, 1973)
Number: 40

The Craftsmen of New France - Moogk, Peter N. (Université de Toronto, 1973)
Keywords: Apprentissage; Artisans

Les industries manufacturières du Québec, 1900-1959: essai de normalisation des données statistiques en dix-sept groupes industriels et étude sommaire de la croissance de ces groupes - Vallières, Marc (Université Laval, 1973)

Joseph Manton - Montreal Gunmaker - Belton, John A. (The Canadian Journal of Arms Collecting, 1972)
Number: 4
Keywords: Armes; Manton; Joseph

LYMAN, BENJAMIN - Armstrong, Frederick H. (Dictionnaire biographique du Canada, 1972)

BECKET, JOHN C - Cooper, John Irwin (Dictionnaire biographique du Canada, 1972)

MOLSON, WILLIAM - Dubuc, Alfred (Dictionnaire biographique du Canada, 1972)

VALOIS, NARCISSE - Lefebvre, Jean-Jacques (Dictionnaire biographique du Canada, 1972)

HODGES, JAMES - Mathieu, Jacques (Dictionnaire biographique du Canada, 1972)

CAMPBELL, ROLLO - Nish, Elizabeth (Dictionnaire biographique du Canada, 1972)

Industrial Land Use in Urban Areas with Special Reference to Montreal - Sharma, Brajesh Chander (Université McGill, 1971)

Quelques méthodes d'évaluation de la structure industrielle d'une région et ses changements comme instrument de l'analyse régionale, appliquée aux secteurs manufacturiers dans deux régions canadiennes: Montréal et Toronto - Siggel, Eckhard (Université de Montréal, 1971)

Région métropolitaine de Montréal: industries manufacturières par ville, 1937-1967 / Metropolitan Montreal: Manufacturing Industries by Cities, 1938-1967 (s.é., 1970)

Les filatures de coton au Québec, 1900-1915 - Rouillard, Jacques (Université Laval, 1970)
Keywords: Chevaliers du Travail; Grèves; Syndicats internationaux; Textile

BROSSARD, URBAIN - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

CHABOULIÉ (Chaboillez), CHARLES - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

FÉZERET, RENÉ - Bazin, Jules (Dictionnaire biographique du Canada, 1969)

Montreal's Dominance of the Canadian Men's Fine Clothing Industry - Davidson, N. Maurice (University of Western Ontario, 1969)
Keywords: Confection; Vêtements

Thomas Molson, entrepreneur canadien, 1791-1863 - Dubuc, Alfred (Université de Paris, 1969)
Keywords: Brasserie; Molson; Thomas

QUESNEVILLE, JEAN - Lahaise, Robert (Dictionnaire biographique du Canada, 1969)

RAIMBAULT, PIERRE - Lahaise, Robert (Dictionnaire biographique du Canada, 1969)

GADOIS, PIERRE - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

PAILLARD, LÉONARD, le Poitevin - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

PAYNE, SAMUEL - Moogk, Peter N. (Dictionnaire biographique du Canada, 1969)

LE CONTE DUPRÉ, LOUIS - Nish, Cameron (Dictionnaire biographique du Canada, 1969)

Centennial/Anniversary Souvenir: A Commemorative Volume Celebrating Canada's Centenary and National Drug's 60 years of Service (National Drug and Chemical Company of Canada, 1967)
Keywords: Commémoration; Lyman; Lyman (famille); Lymans Limited; Produits pharmaceutiques

F. W. Lamplough & J. P. McNaughton - Belton, John A. (The Canadian Journal of Arms Collecting, 1967)
Number: 1
Keywords: Armes; Lamplough & McNaughton

Montréal, métropole industrielle - Germain, Denis (L'Actualité économique, 1967)
issued: 1967-04/1967-06
Keywords: Métropole

Industrial Location in the City of St. Laurent - Isenberg, Seymour (Université McGill, 1967)
Keywords: Saint-Laurent (ville)

Un siècle de progrès; historique de Viau Ltée - Viau, Roger (s.é., 1967)
Keywords: Biscuiterie; Viau (biscuiterie); Viau; Charles-Théodore

PRUD’HOMME, LOUIS - Lefebvre, Jean-Jacques (Dictionnaire biographique du Canada, 1966)

LAUSON, GILLES - Vachon, André (Dictionnaire biographique du Canada, 1966)

Nahum Mower: An Early Printer of Montreal - Colgate, William (s.é., 1964)
Keywords: Imprimerie; Mower; Nahum

A Survey of Industrial Estates with Special Reference to Montreal - Grasser, Otto (Université McGill, 1964)

Le marché des produits du pétrole des raffineries de Montréal - Ménard, Denis (École des hautes études commerciales, 1963)
Keywords: Pétrole

The Elements Combined. A History of The Steel Company of Canada - Kilbourn, William (Clarke, Irwin, 1960)
Keywords: Fer et acier; Montreal Rolling Mills; Pillow-Hersey; Stelco

Géographie manufacturière de Montréal - Beauregard, Ludger (Mélanges géographiques canadiens offerts à Raoul Blanchard, 1959)

The Story of Drummond, McCall & Company Limited, 1881-1956 (Drummond, McCall & Company Limited, 1956)
Keywords: Drummond McCall; Fer et acier

Historique de la Brasserie Dow, 1790-1955 (Brasserie Dow, 1955)
Keywords: Brasserie; Dow (brasserie)

Au pied du courant; l'histoire Molson - Denison, Merrill (Librairie Beauchemin, 1955)
Keywords: Brasserie; Molson (famille)

The Barley and the Stream: The Molson Story - Denison, Merrill (McClelland and Stewart, 1955)
Keywords: Brasserie; Molson (famille)

L'industrie manufacturière dans la zone métropolitaine de Montréal - Harvey, Pierre (L'Actualité économique, 1955)
issued: 1955-04/1955-06

Redpath Centennial, One Hundred Years of Progress 1854-1954 (s.é., 1954)
Keywords: Canada and Dominion Sugar Company; Redpath Sugar; Sucre

Madame de Repentigny - Leland, Marine (Bulletin des recherches historiques, 1954)
Keywords: Saint-Père; Agathe de

L'orfèvre Paul Morand, 1784-1854 - Morrisset, Gerard (Mémoires et comptes rendus de la Société royale du Canada, 1954)
Number: 2
Keywords: Morand; Paul; Orfèvres

The Canadair Story: A Pictorial History of Canada's Leading Aircraft Manufacturer (Canadair, 1952)
Keywords: Avionnerie; Canadair

Ogilvie in Canada, Pioneer Millers, 1801-1951 - Stevens, George R. (Ogilvie Flour Mills Co., 1952)
Keywords: Meunerie; Ogilvie (famille); Ogilvie Flour Mills

Étude comparative des industries manufacturières de Montréal et de Toronto avant et après la guerre - Racine, Louis (École des hautes études commerciales de Montréal, 1951)

The Belding-Corticelli Story 1876-1951 - Stevens, George R. (Belding-Corticelli Ltd, 1951)
Keywords: Belding-Corticelli; Textile

The Economics of Assembly and Transportation of Fluid Milk in the Montreal Area - Shipley, William Charlton (Université McGill, 1950)
Keywords: Lait

L'industrie de la boulangerie dans la province de Québec - Martin, Guy (L'Actualité économique, 1947)
Number: 4
Keywords: Boulangerie

The House of Henry Birks and Sons - George A., Robert (Henry Birks and Sons, 1946)
Keywords: Bijouterie; Orfèvres

Agathe de Saint-Père, Dame Legardeur de Repentigny - Massicotte, E.-Z. (Bulletin des recherches historiques, 1944)
Keywords: Saint-Père; Agathe de

L'industrie manufacturière - Delage, Jean (Montréal économique, 1943)

Notre milieu: Montréal économique V. L'industrie manufacturière - Delage, Jean (L'Actualité économique, 1943)
Number: 4

Dominique Rousseau, maître orfèvre et négociant en pelleteries - Massicotte, E.-Z. (Bulletin des recherches historiques, 1943)
Keywords: Fourrure; Orfèvres; Rousseau; Dominique

Many important drug companies started in little back shops (Canadian Pharmaceutical Journal, 1942)
Keywords: Lyman; Lyman (famille); Lymans Limited; Produits pharmaceutiques

La boulangerie à Montréal avant 1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Number: 3
Keywords: Boulangerie

L'industriel Beaudry et le savant Duchaîne - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Keywords: Beaudry; Pierre; Duchaîne; Amable-Daniel

Le développement industriel de Montréal depuis l'Union à 1900 - Dupont-Hébert, Roger (École des hautes études commerciales, 1940)

Montreal Regional Industrial Pattern as Compared to that of Toronto - Fisher, David (Université McGill, 1940)

L'argentier Huguet-Latour - Massicotte, E.-Z. (Bulletin des recherches historiques, 1940)
Keywords: Huguet-Latour; Pierre; Orfèvres

Une famille d'orfèvres - Surveyer, Édouard (Bulletin des recherches historiques, 1940)
Keywords: Arnoldi (famille); Orfèvres

Le rôle des filiales américaines dans le développement industriel de Montréal - Turcot, Jean (Université de Montréal, 1940)

The History of Brewing Industry in the Province of Quebec - Vaillancourt, E. (G. Ducharme, 1940)
Keywords: Brasserie

The Canadian Manufacturers’ Association: A Study in Collective Bargaining and Political Pressure - Clark, Samuel Delbert (University of Toronto Press, 1939)

The Canadian Manufacturers' Association. A Political Pressure Group - Clark, Samuel Delbert (Revue canadienne d'économique et de science politique / Canadian Journal of Economics and Political Science, 1938)
Number: 4

Montreal and the Indian Trade Silver - Traquair, Ramsay (Canadian Historical Review, 1938)
Number: 1
Keywords: Autochtones; Fourrure; Orfèvres

Le développement industriel de l'est de Montréal - Versailles, Yvan (Université de Montréal, 1938)

Montreal 1786-1936; One Hundred and Fiftieth Anniversary of Molson's Brewery (Molson's Brewery Ltd., 1936)
Keywords: Brasserie; Molson (brasserie)

Molson's Presents "Old Montreal" - Brasserie Molson (Gazette Printing, 1936)
Keywords: Molson (brasserie); Molson (famille); Quartiers; Vieux-Montréal

Molson vous Présente "Le Vieux Montréal" - Brasserie Molson (Gazette Printing, 1936)
Keywords: Molson (brasserie); Molson (famille); Quartiers; Vieux-Montréal

Les chantiers Cantin, à Montréal - Massicotte, E.-Z. (Bulletin des recherches historiques, 1936)
Number: 8
Keywords: Cantin; Augustin; Construction navale

The National Breweries Limited; 25e anniversaire, 1909-1934 (s.é., 1934)
Keywords: Brasserie; National Breweries Limited

Fleury Mesplet: une étude sur les commencements de l'imprimerie dans la ville de Montréal - Fauteux, Aegidius (Papers of the Bibliographical Society of America, 1934)
Keywords: Imprimerie; Mesplet; Fleury

Étude des facteurs qui ont déterminé la localisation de l'industrie à Montréal et dans les banlieues - Martin, Gérald (Revue trimestrielle canadienne, 1934)

Le moulin des seigneurs de Montréal - Lapalice, O. (Bulletin des recherches historiques, 1931)
Number: 3
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Libraires-papetiers-relieurs à Montréal au XVIIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Number: 5
Keywords: Librairie; Reliure

Orfèvres et bijoutiers du Régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Keywords: Bijouterie; Orfèvres

Quelques sculpteurs montréalais sous la domination française - Massicotte, E.-Z. (Bulletin des recherches historiques, 1928)
Keywords: Sculpture

The development of the flour and grist milling industry in Canada (Journal of the Canadian Bankers' Association, 1923)
Keywords: Meunerie

Pierre Prud'homme, un montréalais compagnon de La Salle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1922)
Keywords: Cavelier de La Salle; René-Robert; Prud'homme; Pierre

La Saint-Eloi et la corporation des armuriers à Montréal, au XVIIe siècle - Massicotte, E.-Z. (Bulletin des recherches historiques, 1917)
Keywords: Armuriers

Pierre Prud'homme, compagnon de La Salle - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1914)
Keywords: Cavelier de La Salle; René-Robert; Prud'homme; Pierre

Fleury Mesplet, The First Printer at Montreal - Mclachlan, R. W. (Mémoires et comptes rendus de la Société royale du Canada, 1906)
Keywords: Imprimerie; Mesplet; Fleury